Monoclonal lupus autoantibody secretion by human-human hybridomas. Selection of hybrids by conventional and novel techniques. - Littman, B H (1983)
Autoantibody-secreting hybridomas were produced by somatic cell fusion of B lymphocytes from a patient with systemic lupus erythematosus with two different human myeloma lines. Selection of hybrids formed from one of these cell lines was performed by using aminopterine-containing culture medium as this cell line was deficient in hypoxanthine-guanine-phosphoribosyl transferase (HGPRT). The second myeloma line was not HGPRT-deficient but instead was treated with diethylpyrocarbonate, which assured death of unfused myeloma cells. This novel technique has wide applicability. Hybridomas were found to secrete antibodies to native DNA and to extractable nuclear antigen. The binding specificities of one IgM anti-DNA antibody was characterized and found to be specific for double-stranded DNA and had particular binding affinity for poly(dG) . poly(dC).